2014
DOI: 10.1097/jan.0000000000000048
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Art and Music Therapy in Substance Abuse Treatment Programs

Abstract: While the implementation of evidence-based practices (EBPs) in the treatment of substance use disorders (SUD) has attracted substantial research attention, little consideration has been given to parallel implementation of complementary and alternative medical (CAM) practices. Using data from a nationally representative sample (N = 299) of U.S. substance abuse treatment programs, this study modeled organizational factors falling in the domains of patient characteristics, treatment ideologies, and structural cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 39 publications
(64 reference statements)
1
39
0
2
Order By: Relevance
“…Larger treatment programs tend to have greater slack resources available for implementation of ancillary services (Rogers, 2003). Organizational studies confirm the positive link between organization size and adoption of a variety of treatment services (Abraham et al, 2011; Aletraris, Paino, Bond Edmond, Roman, & Bride, 2014; Pollack & D'Aunno, 2010). Another relevant treatment program resource is staff education, as greater educational attainment facilitates the adoption and implementation of new organizational practices (Cohen & Levinthal, 1990).…”
Section: Introductionmentioning
confidence: 81%
“…Larger treatment programs tend to have greater slack resources available for implementation of ancillary services (Rogers, 2003). Organizational studies confirm the positive link between organization size and adoption of a variety of treatment services (Abraham et al, 2011; Aletraris, Paino, Bond Edmond, Roman, & Bride, 2014; Pollack & D'Aunno, 2010). Another relevant treatment program resource is staff education, as greater educational attainment facilitates the adoption and implementation of new organizational practices (Cohen & Levinthal, 1990).…”
Section: Introductionmentioning
confidence: 81%
“…It is also surprising that music interventions are not more widely used within substance abuse treatment services. A recent study in which 307 substance abuse treatment services in the United States participated reported that fewer than 15% offered music therapy within their programs, and those that did were likely to have a higher percentage of female patients (OR = 1.014) and a higher percentage of adolescent patients (OR = 1.016) (Aletraris, Paino, Edmond, Roman & Bride, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on music therapy have found numerous benefits for patients with substance use disorders. Activities in music therapy in such patients are associated with a decrease in anxiety, depression, anger and stress (Aletraris et al, 2014).…”
Section: In Psychiatrymentioning
confidence: 99%